2021
DOI: 10.3390/foods10092234
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Levels in Milk and Cheese Produced in the Kvemo Kartli Region, Georgia

Abstract: Milk and dairy products are among the most important food sectors in Georgia, and milk is considered one of the most essential foods in the human diet according to Georgian food culture. Kvemo Kartli is one of the major regions in Georgia for milk production. This region suffers from heavy metal contamination in soil and water because of the mining industry. This study was conducted to determine the concentrations of cadmium, lead, iron, zinc, copper, chromium, manganese, cobalt, nickel, selenium and molybdenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
4
18
0
1
Order By: Relevance
“…For this reason, the determination of the heavy metal level in cheeses is very important [ 24 ]. As for the heavy metal concentration in this study, their content was very low, comparable to values reported in the literature [ 24 , 25 , 26 , 27 ]. Lead was below the permissible levels.…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, the determination of the heavy metal level in cheeses is very important [ 24 ]. As for the heavy metal concentration in this study, their content was very low, comparable to values reported in the literature [ 24 , 25 , 26 , 27 ]. Lead was below the permissible levels.…”
Section: Discussionsupporting
confidence: 89%
“…Moreno-Rojas and coworkers [ 17 ] analysed 50 varieties of cheeses made in Spain and reported average levels of toxic metals similar to those determined in the present study. Nevertheless, cheeses made from cow’s milk from polluted regions had higher levels of Pb or As [ 18 , 19 ], whereas in all of these studies the Cd levels were generally low and similar to those in unpolluted areas [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Логічно, що найвищі значення виявлено в екологічно забруднених зонах (Domingo, 2021). Результати дослідження на території Грузії показали, що концентрація токсичних елементів у більшості проб молока була досить постійною для всіх сіл і нижчою за допустимі рівні, за винятком семи проб (AlSidawi et al, 2021).…”
Section: вступunclassified